2006
DOI: 10.1111/j.1600-0501.2006.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Load‐related bone modelling at the interface of orthodontic micro‐implants

Abstract: The purpose of this study was to determine the interface reaction of two different titanium micro-implant systems activated with different load regimens. A total of 200 micro-implants (100 Abso Anchor and 100 Dual Top) were placed in the mandible of eight Göttinger minipigs. Two implants each were immediately loaded in the opposite direction by various forces (100, 300 or 500 cN) through tension coils. Three different distances between the neck of the implant and the bone rim (1, 2, 3 mm) were used. The loads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
15

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 29 publications
4
25
0
15
Order By: Relevance
“…Low-grade microdamage or microcracks are physiologically present in loaded bone [28]. The continuous loading of bone induces active bone remodeling [6,16]. Traumatized bone tissue is thus replaced by newly-formed replacement bone.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-grade microdamage or microcracks are physiologically present in loaded bone [28]. The continuous loading of bone induces active bone remodeling [6,16]. Traumatized bone tissue is thus replaced by newly-formed replacement bone.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…logischen Belastungen des Knochens kontinuierlich neu auf und konnten histologisch auch nach längerer klinischer Verweildauer einer Mikroschraube in situ in direkter Nachbarschaft zum Schraubengewinde nachgewiesen werden [4]. Sie induzieren -zumindest in vitalem Knochen -den aktiven Knochenumbau [6,9,16,17]. So wird solch traumatisiertes Knochengewebe physiologischerweise wieder durch neu gebildeten Ersatzknochen substituiert.…”
Section: Study Animals and Bone Segment Preparationunclassified
See 1 more Smart Citation
“…[31][32][33][34][35] In particular, the contact with the compact bone seems to be important for implant stability. 36 A correlation could found between the bone to implant contact rate and RFA.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent microscopic images are also useful for confirming bone formation in the area surrounding implants (22,23,(30)(31)(32). Deguchi et al (23) used fluorescent and polarized microscopic to evaluate growing dogs and found that mini-implants were able to function as rigid osseous anchors during orthodontic loading for 3 months.…”
Section: Discussionmentioning
confidence: 99%